PERAN GURU SEBAGAI FASILITATOR DIGITAL DALAM IMPLEMENTASI STRATEGI PEMBELAJARAN MAHARAH QIRO’AH ERA DISRUPSI TEKNOLOGI - Umi Hijriyah; Abdurachman Abdurachman; Vivi Dwi Clarissa; Althaf Javid H. Aziz (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2026)
ABSTRACT The era of technological disruption has driven significant changes in Arabic language learning, including maharah qira’ah (reading skills), which require a digital-based approach. This study aims to analyze the role of teachers as digital facilitators in teaching maharah qira’ah and to identify the challenges and solutions associated with its implementation. The study employs a library research method with a descriptive-analytical approach through the stages of identification, selection, critical evaluation, and synthesis of various sources related to educational technology, Arabic language learning, and digital literacy. The findings reveal that teachers acting as digital facilitators can effectively utilize interactive reading applications, Arabic e-texts, podcasts, and instructional videos to enhance students’ reading comprehension. Their roles include serving as content curators, instructional designers, digital literacy mentors, and technology-based evaluators. The main challenges identified are limited digital competencies among some teachers, inadequate infrastructure, and the scarcity of high-quality Arabic digital learning materials. This study recommends strengthening teachers’ digital competencies, providing adequate technological infrastructure, and developing standardized digital qira’ah content. The study concludes that the success of maharah qira’ah learning in the digital era depends largely on teachers’ ability to integrate technology pedagogically. This research contributes to strengthening the concept of teachers as digital facilitators in supporting the development of adaptive, effective Arabic language learning that meets the demands of the twenty-first century. ABSTRAK Era disrupsi teknologi mendorong perubahan dalam pembelajaran bahasa Arab, termasuk pada maharah qiro’ah (kemampuan membaca) yang memerlukan pendekatan berbasis digital. Penelitian ini bertujuan menganalisis peran guru sebagai fasilitator digital dalam pembelajaran maharah qiro’ah serta mengidentifikasi tantangan dan solusi implementasinya. Metode yang digunakan adalah kajian pustaka (library research) dengan pendekatan deskriptif-analitis melalui tahapan identifikasi, seleksi, evaluasi kritis, dan sintesis berbagai sumber terkait teknologi pendidikan, pembelajaran bahasa Arab, dan literasi digital. Hasil penelitian menunjukkan bahwa guru sebagai fasilitator digital mampu memanfaatkan aplikasi membaca interaktif, e-teks Arab, podcast, dan video pembelajaran untuk meningkatkan pemahaman bacaan peserta didik. Peran tersebut mencakup fungsi sebagai kurator konten, perancang pembelajaran, pembimbing literasi digital, dan evaluator berbasis teknologi. Kendala utama meliputi rendahnya kompetensi digital sebagian guru, keterbatasan infrastruktur, dan minimnya bahan ajar digital berbahasa Arab yang berkualitas. Penelitian ini merekomendasikan penguatan kompetensi digital guru, penyediaan infrastruktur yang memadai, dan pengembangan konten qiro'ah digital yang terstandarisasi. Simpulan penelitian menegaskan bahwa keberhasilan pembelajaran maharah qiro’ah di era digital bergantung pada kemampuan guru mengintegrasikan teknologi secara pedagogis. Penelitian ini berkontribusi dalam memperkuat konsep guru sebagai fasilitator digital untuk mendukung pengembangan pembelajaran bahasa Arab yang adaptif, efektif, dan sesuai dengan tuntutan abad ke-21.